Gambaran Karakteristik Dan Pengetahuan Ibu Tentang Pemberian Asi Eksklusif Pada Bayi di Puskesmas Doro I - Tiara Septi Putri Sari; Neti Mustikawati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Mother's milk (ASI) is a source of food for babies which is useful for the growth and development of babies. Providing breast milk for 6 months to newborns is the gold standard for baby feeding recommended by WHO. Even though breastfeeding is very important for babies, mothers also often experience failure in providing exclusive breastfeeding. This research aims to describe the characteristics and knowledge of mothers regarding exclusive breastfeeding for babies aged 0-6 months at the Doro I Community Health Center. This research is a descriptive quantitative study, data collection uses Cluster Sampling where the sample is grouped based on region (Posyandu) or population location by 65 samples. This research instrument uses a Knowledge Questionnaire about Exclusive Breastfeeding adopted from (Septianingrum, 2018) consisting of 19 questions. For favorable questions the